2022
DOI: 10.1093/cid/ciac961
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Long Coronavirus Disease in US Adults

Abstract: Background We estimated the prevalence of long COVID and impact on daily living among a representative sample of adults in the United States (US). Methods We conducted a population-representative survey, June 30-July 2, 2022, of a random sample of 3,042 United States adults aged 18 years or older and weighted to the 2020 US population. Using questions developed by the United Kingdom’s Office of National Statistics, we estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0
7

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 23 publications
7
38
0
7
Order By: Relevance
“…These important findings were confirmed in a subsequent and more recent study including 3042 adults from the United States, who completed a questionnaire in order to define their health and fitness after recovering from an acute SARS -CoV -2 infection. 41 In keeping with previous evidence, long -COVID was found to be more frequent in women (OR, 1.84; 95% CI, 1.40-2.42) and in those with pre -existing comorbidities (OR, 1.55; 95% CI, 1.19-2.34). Moreover, as compared with COVID -19 vaccine recipients who received at least a single booster dose, the unvaccinated individuals had an over 40% higher risk of developing long -COVID (OR, 1.41; 95% CI, 1.05-1.91).…”
Section: Impact Of Sars -Cov -2 Variantssupporting
confidence: 88%
“…These important findings were confirmed in a subsequent and more recent study including 3042 adults from the United States, who completed a questionnaire in order to define their health and fitness after recovering from an acute SARS -CoV -2 infection. 41 In keeping with previous evidence, long -COVID was found to be more frequent in women (OR, 1.84; 95% CI, 1.40-2.42) and in those with pre -existing comorbidities (OR, 1.55; 95% CI, 1.19-2.34). Moreover, as compared with COVID -19 vaccine recipients who received at least a single booster dose, the unvaccinated individuals had an over 40% higher risk of developing long -COVID (OR, 1.41; 95% CI, 1.05-1.91).…”
Section: Impact Of Sars -Cov -2 Variantssupporting
confidence: 88%
“…Impacts on daily activities were severe for 25.3% of those with Long COVID and 28.9% had SARS-CoV-2 infection over a year ago. Women, those with comorbidities, and those unvaccinated or not boosted were at higher risk ( Robertson et al, 2022 ). Studies from the USA and Europe have found that the prevalence of Long COVID is higher among women and those with multiple chronic conditions ( Chen et al, 2022 ; Fernández-de-Las-Peñas et al, 2022 ; Robertson et al, 2022 ; Thompson et al, 2022 ).…”
Section: Insight Into Pasc Disease Patternmentioning
confidence: 99%
“…Women, those with comorbidities, and those unvaccinated or not boosted were at higher risk ( Robertson et al, 2022 ). Studies from the USA and Europe have found that the prevalence of Long COVID is higher among women and those with multiple chronic conditions ( Chen et al, 2022 ; Fernández-de-Las-Peñas et al, 2022 ; Robertson et al, 2022 ; Thompson et al, 2022 ). However, there is variation in risk factor data due to differences in study design, population studied, and definition of Long COVID.…”
Section: Insight Into Pasc Disease Patternmentioning
confidence: 99%
“…Additionally, a slightly larger proportion of long COVID was reported by women in our study, as well as in other studies. [35][36][37][38] In general, the prevalence of long COVID may vary across studies due to differences in sampling, definition, and measurement methods. 31 Prevalence of long COVID may also vary between, but also within, studies due to the timing of data collection.…”
Section: Discussionmentioning
confidence: 99%